Staphylococcus aureus infections: epidemiology, pathophysiology, clinical manifestations, and management - Tong, Steven Y C; Davis, Joshua S; Eichenberger, Emily; Holland, Thomas L; Fowler, Jr, Vance G (Clinical microbiology reviews, 2015)
Staphylococcus aureus is a major human pathogen that causes a wide range of clinical infections. It is a leading cause of bacteremia and infective endocarditis as well as osteoarticular, skin and soft tissue, pleuropulmonary, and device-related infections. This review comprehensively covers the epidemiology, pathophysiology, clinical manifestations, and management of each of these clinical entities. The past 2 decades have witnessed two clear shifts in the epidemiology of S. aureus infections: first, a growing number of health care-associated infections, particularly seen in infective endocarditis and prosthetic device infections, and second, an epidemic of community-associated skin and soft tissue infections driven by strains with certain virulence factors and resistance to β-lactam antibiotics. In reviewing the literature to support management strategies for these clinical manifestations, we also highlight the paucity of high-quality evidence for many key clinical questions.